Community health workers’ involvement in the prevention and control of non-communicable diseases in Wakiso District, Uganda - David Musoke; Edwinah Atusingwize; Deborah Ikhile; Sarah Nalinya; Charles Ssemugabo; Grace Biyinzika Lubega; Damilola Omodara; Rawlance Ndejjo; Linda Gibson (Globalization and Health, 2021)
Abstract Background Community health workers (CHWs) are an important cadre of the global health workforce as they are involved in providing health services at the community level. However, evidence on the role of CHWs in delivering interventions for non-communicable diseases (NCDs) in Uganda is limited. This study, therefore, assessed the involvement of CHWs in the prevention and control of NCDs in Wakiso District, Uganda with a focus on their knowledge, attitudes and practices, as well as community perceptions. Methods A cross-sectional study using mixed methods was conducted which involved a structured questionnaire among 485 CHWs, and 6 focus group discussions (FGDs) among community members. The study assessed knowledge, perceptions including the importance of the various risk factors, and the current involvement of CHWs in NCDs, including the challenges they faced. Quantitative data were analysed in STATA version 13.0 while thematic analysis was used for the qualitative data. Results The majority of CHWs (75.3%) correctly defined what NCDs are. Among CHWs who knew examples of NCDs (87.4%), the majority mentioned high blood pressure (77.1%), diabetes (73.4%) and cancer (63.0%). Many CHWs said that healthy diet (86.2%), physical activity (77.7%), avoiding smoking/tobacco use (70.9%), and limiting alcohol consumption (63.7%) were very important to prevent NCDs. Although more than half of the CHWs (63.1%) reported being involved in NCDs activities, only 20.9 and 20.6% had participated in community mobilisation and referral of patients respectively. The majority of CHWs (80.1%) who were involved in NCDs prevention and control reported challenges including inadequate knowledge (58.4%), lack of training (37.6%), and negative community perception towards NCDs (35.1%). From the FGDs, community members were concerned that CHWs did not have enough training on NCDs hence lacked enough information. Therefore, the community did not have much confidence in them regarding NCDs, hence rarely consulted them concerning these diseases. Conclusions Despite CHWs having some knowledge on NCDs and their risk factors, their involvement in the prevention and control of the diseases was low. Through enhanced training and community engagement, CHWs can contribute to the prevention and control of NCDs, including health education and community mobilisation.